TINJAUAN KRIMINOLOGIS TERHADAP KEBEBASAN SEKSUALITAS ANAK DI KUTAI KARTANEGARA - Dian Puspitasari (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRAK Indonesia is a country that upholds justice can live harmoniously and peacefully so that law enforcement in Indonesia must be upheld. Freedom Child sexuality is one form that can cause negativity for victims.Indonesia as a law state provides protection for every citizen with the enforcement of applicable laws in Indonesia. What are the considerations in this thesis are what factors cause freedom of sexuality for children? and How do you deal with child sexuality in Kutai Karatenegara according to law? Sources of data that can be obtained from the author are obtained from books and laws and regulations relating to the existing debate.Based on the conclusions, the authors suggest that prevention has been carried out by the police which involves the spread of schools such as elementary schools, junior high schools, and high schools and also controls in places reviewed by researchers conducting research on moral norms, also as parents too. participate in the obligation to provide guidance on the development of children and the imposition of appropriate penalties by judges as repressive efforts.Keywords ; Children, Sexual Freedom.